Investigating the Impact of Perceived Value and Customer Satisfaction on Repurchase Intentions Among Female E-Commerce Customers - Oktaviani, Rizki (Klabat Journal of Management, 2024)
This study investigates the impact of perceived value and customer satisfaction on repurchase intentions, focusing specifically on Shopee's customer base. Employing a quantitative approach with a descriptive methodology, primary data was collected through online questionnaires distributed to female Shopee customers. A total of 100 questionnaires were gathered using purposive sampling, targeting females with previous Shopee purchases. Data analysis utilized SPSS and included validity and reliability testing, coefficient of determination, hypothesis testing, as well as partial and simultaneous testing. Additionally, multiple linear regression analysis was conducted. Results indicate a significant positive influence of perceived value and customer satisfaction on repurchase intentions. Recommendations for Shopee include prioritizing aspects such as shopping convenience, pricing, product quality, and order processing time to enhance perceived value and encourage repurchase intention.